The rheological characteristics of soy protein isolate-glucose conjugate gel during simulated gastrointestinal digestion. (July 2021) - Liu, Feng; Feng, Sirui; Guo, Yunsi; Li, Zhangpeng; Chen, Lichun; Handa, Akihiro; Zhang, Yue
Graphical abstract: Highlights: Gels were prepared using soy protein isolate-glucose conjugates cross-linked by transglutaminase. The mechanical properties of gels were increased by glycation with limited reaction time. The rheological properties of SPI-glc conjugate and mixture gels after in vitro gastrointestinal digestion have been studied. Conjugate gels had slower gastric digestion kinetics than gel prepared by SPI-glc mixture. There were no differences in simulated intestinal digestion among SPI-glc conjugate and mixture gels. Abstract: In this study, soybean protein isolate (SPI) and glucose (glc) were conjugated by wet Maillard reaction at 95 °C for 0–6 h with a mass ratio of 1:2. The degree of grafting and SDS-PAGE of SPI-conjugates were studied and a highest degree of grafting (23.14 %) was achieved at reaction time of 4 h. Gels were then prepared by crosslinking SPI-glc mixture or conjugates using transglutaminase, and their mechanical properties were charactered by hardness and gumminess. To further study the impact of conjugation on the gastrointestinal digestion of gel, rheological properties of gels after in vitro gastric and intestinal digestions were evaluated through amplitude and frequency sweep tests. Compared with SPI and SPI-glc mixture, gels formed by conjugates with 1 h and 4 h reaction time showed significantly higher viscosity, storage modulus (G') and complex modulus (G*) values after gastric digestion, indicating that these conjugate gels had slower gastric digestion kinetics. There were no significant differences among these samples in simulated intestinal digestion. Therefore, the SPI-glc conjugate gels may have great potential to be used for gastric delivery.